2018
DOI: 10.1002/da.22766
|View full text |Cite
|
Sign up to set email alerts
|

Associations between therapists' occupational burnout and their patients' depression and anxiety treatment outcomes

Abstract: Therapist burnout has a negative impact on treatment outcomes and could be the target of future preventive and remedial action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 34 publications
(53 reference statements)
5
107
0
1
Order By: Relevance
“…Supporting the wellbeing of health professionals is important for a number of reasons. Firstly, health professionals who are burnt out are more likely to make errors and client outcomes can be compromised (Delgadillo, Saxon & Barkham, 2018;Salyers et al, 2015). Secondly, health professionals who are dissatisfied with their positions are more likely to leave their jobs which can lead to loss of institutional knowledge, increased recruitment and training costs, disruption in therapeutic relationships and continuity of care and may impact on the roll out of evidence based practices (Jones, 2004;O'Brien-Pallas et al, 2006;Ray, Wong, White & Heaslip, 2013;Woltmann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting the wellbeing of health professionals is important for a number of reasons. Firstly, health professionals who are burnt out are more likely to make errors and client outcomes can be compromised (Delgadillo, Saxon & Barkham, 2018;Salyers et al, 2015). Secondly, health professionals who are dissatisfied with their positions are more likely to leave their jobs which can lead to loss of institutional knowledge, increased recruitment and training costs, disruption in therapeutic relationships and continuity of care and may impact on the roll out of evidence based practices (Jones, 2004;O'Brien-Pallas et al, 2006;Ray, Wong, White & Heaslip, 2013;Woltmann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study potentially suggest some of the factors that may explain the variable effectiveness of NHS psychological therapy services. The results also suggest some of the factors that are responsible for practitioner burnout, which has also been found to have a measurable negative impact on NHS client outcomes in therapy (Delgadillo et al., ). This study thus contributes to a growing literature on the concerning impacts on clients of the current NHS context.…”
Section: Discussionmentioning
confidence: 68%
“…The third possibility is that our particular measures of workload did not effectively tap the underlying construct of work demands for psychological therapists. Delgadillo et al (2018) favoured this third explanation in their study, but further research would be necessary to establish which types of demands may be most relevant for psychological therapists in the United Kingdom. Fourth is the possibility that the association between some workload factors such as caseload and burnout in psychological therapists is weak and unlikely to replicate in every study.…”
Section: Discussionmentioning
confidence: 94%
“…However, these recent studies were conducted outside the United Kingdom, and the present findings could be due to the UK healthcare delivery context, studies of NHS‐based therapists are more consistent with our present findings. For example, in a mixed sample of psychological practitioners working in UK primary care, Delgadillo, Saxon, and Barkham (2018) found that caseload size and severity were not linked with burnout. Similarly, in a group of PWPs and CBT therapists, Westwood et al (2017) found that while overtime was associated with higher burnout in PWPs, there was no association in CBT therapists.…”
Section: Discussionmentioning
confidence: 99%